Identification and validation of ferroptosis-related gene signature in intervertebral disc degeneration - Xiang, Qian; Zhao, Yongzhao; Li, Weishi (Frontiers in Endocrinology, 2023)
Lower back pain (LBP) is a leading cause of disability in the elderly and intervertebral disc degeneration (IDD) is the major contributor to LBP. Ferroptosis is a newly discovered programmed cell death, characterized by iron-dependent lethal lipid peroxidation. Growing evidence has shown that ferroptosis plays important roles in various human diseases. However, the underlying mechanism of ferroptosis in IDD remains elusive. This study is aimed to uncover the key roles of ferroptosis in the pathogenesis and progression of IDD comprehensively. To investigate the ferroptosis related differentially expressed genes (FRDEGs) in IDD, we analyzed the microarray data from the Gene Expression Omnibus (GEO) database. Then we performed functional enrichment analysis and protein-protein interaction (PPI) network analysis, and screened out the hub FRDEGs. To further evaluate the predictive value of these hub FRDEGs, we performed ROC analysis based on the GSE124272 dataset. A total of 80 FRDEGs were identified, including 20 downregulated and 60 upregulated FRDEGs. The FRDEGs were primarily involved in the biological processes of response to chemical, and response to stress. KEGG pathway enrichment analysis showed that the FRDEGs were mainly involved in ferroptosis, TNF signaling pathway, HIF-1 signaling pathway, NOD-like receptor signaling pathway, and IL-17 signaling pathway. Ten hub OSRDEGs were obtained according to the PPI analysis, including HMOX1, KEAP1, MAPK1, HSPA5, TXNRD1, IL6, PPARA, JUN, HIF1A, DUSP1. The ROC analysis and RT-qPCR validation results suggested that most of the hub FRDEGs might be potential signature genes for IDD. This study reveals that ferroptosis might provide promising strategy for the diagnosis and treatment of IDD.